Applying Q method to Identify and Prioritize Rural Housing Design Aspects - Tohid Hatami Khaneqhai; Akbar Zargar; Mohsen Sartipipour (صفه)
One of key challenges in rural housing design is the misinterpretation of residents’ actual needs and preferences. Incorrect assumptions about user preferences usually lead designers to propose standard solutions insensitive to users’ culture and mentality. The Q methodology is a form of factor analysis that is used to analyze correlations between subjects across a sample of variables. Therefore, it reduces the many individual viewpoints of the subjects down to a few factors, which represent shared ways of thinking. The sample of statements for a Q sort is drawn from a “concourse”, i.e. the sum of all things people say or think about the issue being investigated. The Q method commonly uses a structured sampling approach in order to test and represent the full breadth of a concourse. This paper employs Q methodology to investigate housing preferences in Jailanabad Village close to Isfahan City. It indicates that in contrast with initial assumptions, there is a marked difference among villagers regarding their housing characteristics. For lower-income residents, the key housing priorities are the costs of construction and obtaining legal permits. These residents prefer inexpensive small houses, which could be built with minimal municipal procedures. On the other hand, the high-income villagers prefer housing which boasts their affluence and prestige. Accordingly, they prefer buildings taller than one storey with façade decorations symbolizing their social status.